THE KEDUREI AGUNG TRADITIONAL CEREMONY AS THE CULTURAL IDENTITY OF THE CURUP CITY SOCIETY IN 2000-2018 - Muhammad Deppendra; Alian Alian; Syarifuddin Syarifuddin (Sosiohumaniora, 2022)
This study discusses the Kedurei Agung Traditional Ceremony as the cultural identity of the Curup community in 200-2018. This study aims to strengthen the identity of the Kedurei Agung Traditional Ceremony as the culture of the Curup City community in 2000-2018. Cultural identity is a basic awareness of the special characteristics of a person’s group in terms of living habits, customs, language, and values, meanwhile the Kedurei Agung Traditional Ceremony is one of the traditional ceremonies that has been carried out for a long time by the people of Curup City as respect for ancestors who have passed down the culture and built Curup City. The Kedurei Agung Traditional Ceremony is carried out with the condition that the Corner Prayer is carried out one day before the Kedurei Agung Traditional Ceremony is held. In its implementation, the people of Curup City also offer various harvests that are harvested during the harvest season, the harvests will be distributed and eaten together which indicates the prosperity and welfare of Curup City. The research process was carried out using the historical method with four stages, namely heuristics, source criticism, interpretation, historiography. Data was collected by using literature study, observation, and interview methods. A literature study was conducted on several literatures related to the research topic, observations were made in Curup City, and interviews were conducted with the Curup City Government and the Rejang Lebong District Customary Council. The results show that the Kedurei Agung Traditional Ceremony is a strong cultural identity for the people of Curup City. This is because the Kedurei Agung Traditional Ceremony is an annual event that is routinely carried out by the people of Curup City as a sign of respect for the ancestors and a symbol of the prosperity of Curup City. Along with this, the Kedurei Agung Traditional Ceremony has also developed from 2000 to 2018, this shows that the cultural identity of the Kedurei Agung Traditional Ceremony is getting stronger with conservation efforts from various parties, namely the government, society, and cultural activists.